Dødshjelp i Norden? Etikk, klinikk og politikk - Horn, Morten A.; Kleiven, Daniel Joachim H.; Magelssen, Morten (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
"'Should assisted dying be legal?' is a question that has been and continues to be actively discussed throughout the Western world, leading several countries to change their laws in recent years. This anthology provides a thorough introduction to the question from a Nordic perspective. Contributing authors from Norway, Sweden, Denmark and Finland present the legal frameworks, practices and debates unique to each country. The book gives a broad overview of the issue and also conveys research and experiences from the Netherlands, the United States and Canada. The book has a clear tenor - in the form of a critical stance toward legalization. The primary emphasis is on arguments against legalization, although arguments in favor of legalization are also examined. An objective with this book is to advance the public exchange of opinion, and the authors put forth suggestions for common terminology and identify different tracks in the debate. Assisted Dying in the Nordic Countries? Ethics, Experience and Politics is an important book for those who wish to immerse themselves deeply in the question of assisted dying and the debate on legalization. The book is written for a broad audience, but will be particularly relevant for healthcare workers, students in medicine, other health-related fields and ethics, as well as politicians and journalists. The authors have varied backgrounds within medicine, philosophy, medical ethics, theology and linguistics, and they elucidate the question for a variety of professional and personal perspectives."